Data Issues in Spatial Electric Load Forecasting - Melo, J. D. [UNESP]; Padilha-Feltrin, A. [UNESP]; Carreno, E. M.; IEEE (Ieee, 2014)
The magnitude and geographic location of electricity demand in the planning horizon are vital pieces of information for power distribution companies in planning future network expansion and operation. Such information is often obtained through spatial load forecasting. Several methods have been developed using different data sources as inputs, depending on their availability; however, many of the advanced spatial load forecasting methods have not yet been widely used because of the size, variety, and availability of the data required. This paper presents a review of the different spatial load forecasting techniques developed in the last 10 years, focusing particularly on the evolution of the required input data, as well as some insights on how current and future technologies could be used to improve spatial load forecasting practices.
Keywords: Expansion planning of distribution system; geographic information system; power distribution system; spatial load forecasting